Kilka słów o i-votingu - Skotnicki, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
I-voting is a new alternative way of voting which, apart from Estonia, has been experimentally used in several other countries. However, the analysis made leads to the conclusion that it should be approached with proper caution. This is an interesting experiment, the widespread use of which is a matter of the future, which can not even be approximated. There is too much doubt about this way of voting, it has not contributed to visible growth attendance during the elections, there is also no certainty about the absence of system errors. And though in Poland proposals have been submitted to establish this method of voting, it seems reasonable to doubt whether the benefits in this case will exceed the costs of its implementation and maintenance.
Keywords: e-voting; elections; voting; i-voting; alternative methods of voting